Trade-offs between seed and leaf size (seed–phytomer–leaf theory): functional glue linking regenerative with life history strategies … and taxonomy with ecology?. (27th July 2017) - Hodgson, John G; Santini, Bianca A; Montserrat Marti, Gabriel; Royo Pla, Ferran; Jones, Glynis; Bogaard, Amy; Charles, Mike; Font, Xavier; Ater, Mohammed; Taleb, Abdelkader; Poschlod, Peter; Hmimsa, Younes; et al.
Abstract: Background and Aims While the 'worldwide leaf economics spectrum' (Wright IJ, Reich PB, Westoby M, et al. 2004. The worldwide leaf economics spectrum. Nature 428 : 821–827) defines mineral nutrient relationships in plants, no unifying functional consensus links size attributes. Here, the focus is upon leaf size, a much-studied plant trait that scales positively with habitat quality and components of plant size. The objective is to show that this wide range of relationships is explicable in terms of a seed–phytomer–leaf (SPL) theoretical model defining leaf size in terms of trade-offs involving the size, growth rate and number of the building blocks (phytomers) of which the young shoot is constructed. Methods Functional data for 2400+ species and English and Spanish vegetation surveys were used to explore interrelationships between leaf area, leaf width, canopy height, seed mass and leaf dry matter content (LDMC). Key Results Leaf area was a consistent function of canopy height, LDMC and seed mass. Additionally, size traits are partially uncoupled. First, broad laminas help confer competitive exclusion while morphologically large leaves can, through dissection, be functionally small. Secondly, leaf size scales positively with plant size but many of the largest-leaved species are of medium height with basally supported leaves. Thirdly, photosynthetic stems may represent a functionally viable alternative to 'small seeds + large leaves' in disturbed, fertile habitats and 'large seeds + small leaves' in infertile ones. Conclusions Although key elements defining the juvenile growth phase remain unmeasured, our results broadly support SPL theory in that phytometer and leaf size are a product of the size of the initial shoot meristem (≅ seed mass) and the duration and quality of juvenile growth. These allometrically constrained traits combine to confer ecological specialization on individual species. Equally, they appear conservatively expressed within major taxa. Thus, 'evolutionary canalization' sensu Stebbins (Stebbins GL. 1974. Flowering plants: evolution above the species level . Cambridge, MA: Belknap Press) is perhaps associated with both seed and leaf development, and major taxa appear routinely specialized with respect to ecologically important size-related traits.